Innovations in Islamic Banking on Conventional Banks (Study on Banking Industry Players) - Irsyad Kamal; Yudi Azis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
To answer how big the rate of innovation made by Islamic Banks compared to conventional Banks from the perspective of banking industry players and to find out which innovations need to be improved so that Islamic Banks can compete with Conventional Banks. The research method used is quite easy, starting with a study using 100 samples of Islamic banking industry players and 100 samples of conventional banking industry players domiciled in the city of Bandung. Using the independent samples T-test, it can be seen that innovation in Islamic banks is still below the average compared to conventional banks. The use of the Independent-Samples T Test method for non-parametric statistics (Man Whitney U-Test) was used to evaluate the mean difference between two groups of unrelated samples. The results obtained are quite unique where a test is carried out whether it is true that Islamic banks are considered as innovations from conventional banks.